The customering method : from CX dogma to customer science - Spinley, Aarron (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Despite the promise of enhanced customer engagement through new technology, consumer trust has suffered widespread collapse, and annual corporate losses are in the trillions. This book exposes the faulty foundation of the populist Customer Experience (CX) movement, upturns long-held beliefs in its effectiveness, and details an alternative - industrial - approach to the customer asset base. Aarron Spinley is recognized as a foremost mind in the realm of customer science and strategy. His work helps us to understand - and extract - customer value based on evidence, and in so doing, influences our relationship with technology for better results. The Customering Method marries the sciences and managerial precedent with contemporary capability: optimizing the intersection with marketing, mitigating risk and attrition rates, increasing sales propensity, and boosting profitability. Throughout, Spinley provides practical examples that are relatable, actionable and defensible. These concepts have already influenced senior leaders, CEOs, Chief Marketing Officers, and Directors of Customer Experience across many organizations. Now in published form, this is perhaps the most important book in the field for decades"--
Professions and industrial management -- The marketing method -- The customering method -- Pillar 1 : identity -- Pillar 2 : intent -- Pillar 3 : interactions -- Pillar 4 : measurement and reporting -- Managing the collision -- Correcting the record -- Epilogue -- closing the loop.
Keywords: Customer relations -- Management; Consumer satisfaction; BUSINESS & ECONOMICS / Customer Service; BUSINESS & ECONOMICS / Consumer Behavior; BUSINESS & ECONOMICS / Marketing / General